A phenomenological study of compassion satisfaction among social work educators in higher education - Shubair, Sultan A.; Miller, Ben; Zelenko, Jean (Frontiers in Psychology, 2023)
Compassion satisfaction (CS) is a phenomenon that has been studied among the helping professions, such as nursing and social work and has been linked to stress, burnout, compassion fatigue, and vicarious trauma. Social work educators may also experience these same issues, yet more research is needed on how they might counter the negative impacts associated with this type of work by utilizing their experiences of CS. Thus, this study seeks to explore and describe how this population experiences CS. Eleven in-depth interviews with social work educators were conducted, and constructivist grounded theory techniques were utilized to analyze the data.Social work educators experienced CS within the education and personal realms, which encompassed four different elements: achievement, support, balance, and empathy. These elements were utilized by social work educators in this study as coping strategies to enhance their experience of CS, thus encountering threats to CS, such as institutional barriers, interaction with administrators and colleagues, and work overload. Interventions fostering compassion satisfaction and reducing compassion fatigue, burnout, and stress should be considered, including interventions that increase the sense of accomplishment, promote holistic self-care, encourage administrative and collegial support, and improve work-life balance.